Effect of feeding Thymolina® powder on the carcass characteristics and morphology of small intestine in ross 308 broiler chickens - Hosseini, Seyyedmousa; Chamani, Mohammad; Seidavi, Alireza; Sadeghi, Ali Asghar; Ansari-Pirsaraei, Zarbakht (Acta Scientiarum. Animal Sciences, 2017)
In the present experiment, 320 one day old Ross 308 broiler chickens were used completely randomized design with 4 treatments, 4 replicates, and each replicate contained 20 broiler chickens. Experimental treatments include control, 0.5, 1, and 2% of Thymolina powder in chickens’ diet. Thymolina® is an anti-bacterial powder drug which is made by composing 4 medicinal plants. A significant difference observed between treatments in each parameter of the Intestinal morphology (villus height, villus width, crypt depth and epithelial thickness). Goblet cells number was not affected. Our findings indicated that using Thymolina® in the diet of broiler chickens causes improvements in carcass characteristics. Therefore, it may improve the carcass characteristics and morphology of small intestine in broiler chickens.